Recent advances in ultrathin materials and their applications in e‐skin - Wenchao Gao; Jiaoya Huang; Jiang He; Runhui Zhou; Zemin Li; Ziyu Chen; Yufei Zhang; Caofeng Pan (InfoMat, 2023)
Abstract Intelligent technologies based on artificial intelligence and big data hold great potential for health monitoring and human–machine capability enhancement. However, electronics must be connected to the human body to realize this vision. Thus, tissue or skin‐like electronics with high stretchability and low stiffness mechanical properties are highly desirable. Ultrathin materials have attracted significant attention from the research community and the industry because of their high performance and flexibility. Over the past few years, considerable progress has been made in flexible ultrathin sensors and devices based on ultrathin materials. Here, we review the developments in this area and examine representative research progress in ultrathin materials fabrication and device construction. Strategies for the fabrication of stretchable ultrathin materials and devices are considered. The relationship between the thin‐film structure and performance is emphasized and highlighted. Finally, the current capabilities and limitations of ultrathin devices were explored.